Patients' views of consent in clinical trials for acute myocardial infarction: impact of trial design. Issue 8 (30th December 2016) - Dickert, Neal W; Hendershot, Kristopher A; Speight, Candace D; Fehr, Alexandra E
Abstract : Objective: Seeking prospective informed consent is difficult in clinical trials for emergent conditions such as acute myocardial infarction (AMI). Prior data suggest that enrolment decisions of patients are often poorly informed in AMI trials but that patients prefer to be asked permission before enrolment. It is unknown whether this is true across trial designs or in comparative effectiveness research (CER) with approved treatments. Methods: Structured interviews were conducted with 30 patients with AMI. Participants considered three scenarios: (1) a CER trial of approved antiplatelet drugs; (2) a placebo-controlled trial of a novel drug to reduce myocardial injury and (3) a CER trial of an intra-aortic balloon pump versus medication. Participants were asked their desired involvement in enrolment decisions and willingness to participate. Descriptive analysis was performed of Likert scale data, and qualitative descriptive analysis was performed of textual data. Results: Across scenarios, most participants (73%–80%) preferred to be asked permission prior to trial enrolment. Reasons for involvement included wanting to be the decision maker and a desire for transparency. Willingness to enrol was affected by trial type. Fewer participants stated they would likely enrol in a CER procedural trial than in a CER trial of approved medications (p=0.012). Conclusions: These findings suggest that patients prefer prospective involvement in enrolment decisions to enrolment without consent across trial types. However, their desire to participate was affected by trial type. There is a need to develop and evaluate context-sensitive approaches to consent in AMI trials that account for both the acuity of the situation and trial characteristics.